Infância e cidadania : o que dizem as crianças? - Seganfredo, Nágila de Moura Brandão (2012)
This dissertation has as its main theme the intersection of phenomena "childhood" and "citizenship" in order to analyze their approaches and departures through Brazil's history, documents, legislation and studies on the subject. To this end, we seek to understand what children have to say about their experiences of citizenship and the meanings they attribute to this concept. As theoretical references, has studies the sociology of childhood about the child role in the social scene and also the concept of interpretive reproduction, coined by William Corsaro. The Field research, with eight months in duration, held in the city of Rondonopolis, Mato Grosso, Brazil, in a lower middle-class neighborhood, and with the participation of six children, between 5 and 11 years, with four girls and two boys. To conduct this research, we chose to hold press conferences in the very neighborhood where children live, recorded with digital camera for analysis of behaviors, gestures, looks, also understood as important elements in the discursive production. The themes that guided encounters with children were: family, city, consumer, media, justice, security, rights and duties. The discourses produced in the interactions established between the researcher and the kids are analyzed based on the concepts of dialogism and alterity, coined by Mikhail Bakhtin. The results point to distinctions as to gender, in relation to the ways of valuing participation in public life, highlighted when the boys disparage any merit or right of women, especially when they occupy positions of social status and power, as well as movement in the city. The survey results showed that children know their rights and duties and know the importance of education / civilization, which can be seen at times when children with regard to gender, united to defend their rights, when mean city as a space steeped in violence and therefore should not be frequented by children, and to understand that violence, assisted in the neighborhood and through the television, imposes a scenario of hopelessness and pessimism in relation to the future.